Pengenalan Rapor Pendidikan pada SDN 2 Taman Ayu - Sujaya, Ketut Ary; Amniatin Naqiyah; Baiq Elda Dinisa Putri; Bq. Meli Reksa Heriani; Arma Sentia Lestari; Ratih Puspita Sari; Rabiatul Adawiyah; Refani Pramunita (Pendidikan Matematika, FKIP Universitas Mataram, 2024)
Rapor Pendidikan is one of the platforms provided by the Ministry of Education, Culture, Research and Technology. This platform displays the results of the school's Computer-Based National Assessment and Data-Based Planning. SDN 2 Taman Ayu is one of the schools in West Lombok that has not yet taken full advantage of this platform. This has an impact on the lack of information obtained so that the real problems that occur in schools are difficult to know. This service activity aims to disseminate the Rapor Pendidikan at SDN 2 Taman Ayu so that later it can be used as a support to find out the real problems that are occurring so that the school can prepare targeted plans to resolve these problems based on data in the field. The target of this dissemination is all educational staff at SDN 2 Taman Ayu. From this dissemination, the school know the real problems that are occurring and will design improvements programs as a solution to these problems